Preliminary Survey of Composition, Generation and Management of Solid Wastes in Ward 7, Soc Trang City, Soc Trang, Vietnam - Giao, Nguyen Thanh (International Journal of Environment, Agriculture and Biotechnology, 2020)
This research was to investigate the current status of solid waste generation, composition and management in Ward 7, Soc Trang City, Soc Trang Province through interviewing the households of understandings and practices with solid wastes and the placing the plastic bags for collecting the generated wastes directly at the households for compositional analysis. The results showed that organic matter accounted for 62.31%, recyclable and reusable items such as plastic accounted for 19.61%, paper occupied 14.55%, glass took 1.16 %, accounted for 0.79%, cloth occupied 1.69% and foam took 0.74%. Hazardous waste only accounted for a small proportion (0.11%). The average rate of solid waste generation was 0.91 kg/household/day and the average waste generation rate per person was 0.22 kg/person/day. Currently, the management, collection and transportation of domestic solid wastes in the ward 7 has not been guaranteed, not yet effective, causing several environmental problems; open dumping is still commonly seen in the study area due to lack of sanitary landfills. Local authority should take proper measures to effectively manage solid wastes in Ward 7, Soc Trang City, Soc Trang province.